Politeknik Harapan Bersama’s Students’ Perception To English Club Related To English Ability Enhancement - MUCHAMMAD SOFYAN FIRMANSYAH; SYAEFANI ARIF ROMADHON (Universitas Negeri Medan, 2023)
Poltek English Club (PEC), which is a student activity unit, is asked to become an agent of change that changes students' perceptions to speak English as an active language. Even so, the existence of PEC at Politeknik Harapan Bersama is still very young. This requires research whether this PEC has an impact on improving the English language skills of Politeknik Harapan Bersama students. Research conducted using data triangulation; observation, interview and documentation. The results of this study are the perceptions of Politeknik Harapan Bersama students towards the existence of the English Club (PEC) Polytechnic on their English language skills. There are three dominant perceptions found. The first is that joining PEC is not interesting, as they are learning English as the lesson in the class. The second is the students feel that they are already mastered English as they are learning it from the elementary school until college. The third is they don’t interest in learning English as it is not use directly to speak with the foreigner as they don’t go to other English spoken countries. The conclusion of this research is many students of Politeknik Harapan Bersama do not perceive PEC as an interesting activities to be followed. Thus, PEC managements should think a solution to boost students’ curiosity and interest. Keywords: College, English Club, Politeknik Harapan Bersama, Perception.